Study of the effect of Lactobacillus crispatus FSCDJY67L3 on Helicobacter Pylori eradication: a double-blind randomized controlled clinical trial - Hong, Qing; Wang, Jidong; Zhang, Huayue; Liu, Xiaoming; Liu, Zhenmin (Frontiers in Immunology, 2023)
Helicobacter pylori (H. pylori) is a gram-negative bacterium exhibiting high pathogenicity. Traditional antibiotic treatments are considered ineffective as the H. pylori resistance has increased. Recently, a quadruple therapy strategy of probiotics and antibiotics to eliminate H. pylori was proposed. Probiotics play a therapeutic role as supplements in this process. The present research screened a probiotic strain (Lactobacillus crispatus FSCDJY67L3) that co-aggregates strongly with H. pylori. L. crispatus FSCDJY67L3 was demonstrated to significantly reduce H. pylori load (14C breath test) in clinical trials with H. pylori-positive patients. The Gastrointestinal Symptom Rating Scale (GSRS) score decreased, indicating improvement in the gastrointestinal discomfort of patients. Furthermore, L. crispatus FSCDJY67L3 showed no change in the structure of the intestinal flora of patients. Routine blood indices and blood biochemical indices related to liver and kidney function were also not affected in the patients. Therefore, L. crispatus FSCDJY67L3 may be used clinically as a supplement for the treatment of H. pylori. Clinical Trial Registration https://www.chictr.org.cn/, Chinese Clinical Trial Registry (ChiCTR2100053710).